Peran Pemerintah Negeri dalam Pelestarian Tradisi Pukul Sapu Lidi di Mamala - Tazqia Amelia Makatita; Stanislaus Kostka Ohoiwutun; Ivonny Yeany Rahanra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the role of the negeri government in preserving the Pukul Sapu Lidi tradition in Mamala, Leihitu District, Central Maluku Regency. The research is grounded in the urgency of local cultural preservation amid modernization, digital entertainment, and declining youth involvement in traditional practices. Pukul Sapu Lidi, also known locally as Baku Pukul Manyapu, is not merely a cultural attraction but a symbolic expression of solidarity, courage, historical memory, and the healing tradition associated with Minyak Mamala. This study employed a descriptive qualitative approach through observation, interviews, and documentation. The informants consisted of the head of Mamala negeri, negeri apparatus, customary leaders, and community members who understand the implementation of the tradition. The findings show that the negeri government plays several important roles, namely as facilitator, dynamizer, regulator, innovator, motivator, and communicator. These roles are reflected in support for annual cultural activities, coordination with customary and religious actors, moral encouragement to the community, and efforts to introduce the tradition to wider audiences. However, preservation still faces obstacles such as limited budgeting, weak formal regulation, inadequate documentation, and limited involvement of younger generations. The study implies that cultural preservation requires stronger local policy, systematic documentation, intergenerational education, and collaboration between the negeri government, customary institutions, schools, and tourism stakeholders.